Perkembangan Industri Pengolahan di Kota Banjarmasin - Rizki, Ghiyats Maraya (PPJP ULM, 2018)
This study aims to examine the factors that affect the economic growth of the processingindustry sector in Banjarmasin. Independent variables in this research are the Numberof Business Unit of Processing Industry, Processing Industry Investment, andProcessing Industry Worker; dependency is the economic growth of the processingindustry sector in Banjarmasin City. The data analyzed in this study is time-series data obtained from the CentralBureau of Statistics Banjarmasin. The data analysis technique used is regressionanalysis by using a semi-log. Before the research, the first classic assumption test todetect multikolineritas, heteroskedasticity and autocorrelation. Research shows that only the variable of the business unit partially influencesto the economic growth of the processing industry sector in Banjarmasin City. Togetherwith the variables of the business unit, investment and labor influence the economicdevelopment of the processing industry sector in Banjarmasin City.